2020
DOI: 10.3390/biomimetics5040056
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Biomimetic Composite Materials to Acidic Challenges: Influence on Flexural Resistance and Elastic Modulus

Abstract: Acidic conditions of the oral cavity, including soft drinks and cariogenic bacteria, represent a damage for restorative biomimetic composite materials. The aim of this study is to assess the influence of two different acidic challenges on the flexural strength and elastic modulus of five composites: x-tra fil (Group 1, XTF), GrandioSO x-tra (Group 2, GXT), Admira Fusion x-tra (Group 3, AFX), VisCalor bulk (Group 4, VCB), and Enamel Plus HRi (Group 5, EPH). Thirty samples for each group were randomly divided an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Compared to conventional composites, VC is composed of a higher percentage of filler content (83%). This may have influenced modulus development within the restoration [ 42 ], i.e., leading it to exhibit a more compliant biomechanical behavior in the study. Moreover, VC presents a greater depth of cure and generates less polymerization stress when compared with conventional formulations, thereby, positively influencing the restoration resistance to fatigue [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to conventional composites, VC is composed of a higher percentage of filler content (83%). This may have influenced modulus development within the restoration [ 42 ], i.e., leading it to exhibit a more compliant biomechanical behavior in the study. Moreover, VC presents a greater depth of cure and generates less polymerization stress when compared with conventional formulations, thereby, positively influencing the restoration resistance to fatigue [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This stress concentration can lead to cohesive failures in the cement layer. These flaws, in constant contact with oral fluids and other influencing factors, could increase the marginal infiltration that, in the long-term, can culminate in damages in the tooth structure and pulp [ 54 , 55 , 56 ]. Although the nanotechnology has brought improvements to the field of nanomedicine, providing improved materials that are able to mimic human body tissues to a certain point, there are still many challenges to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Based on other authors’ observations, it can be concluded that longer immersion in the beverages would result in statistically significant changes [ 28 ]. On the other hand, Scribante et al obtained a statistically significant decrease in flexural strength of composite resin after soaking in Coca-Cola after 7 days [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%